Effect of Al2O3 addition on dielectric, piezoelectric and ferroelectric properties of O.2Pb(Zn1/3Nb2/3)O 3-0.8Pb(Zr1/2Ti1/2)O3 ceramics - A. Ngamjarurojana (2018)
The structure and electrical properties of Al2O 3-doped 0.2Pb(Zn1/3Nb2/3)O3-0. 8Pb(Zr1/2Ti1/2)O3 ceramic, which is the morphotropic phase boundary composition of the PZN-PZT system, were investigated. The addition of Al2O3 content transformed the crystal structure from coexisting with rhombohedral to purely tetragonal structure. Furthermore, addition of Al2O3 decreased εr, d33 and kp, but increased Curie temperature and enhanced the mechanical quality factor. Finally, the P-E and s-E loops demonstrated decreased Pr, Ec and strain level with addition of Al2O3. © 2008 Trans Tech Publications, Switzerland.